Designing a model for knowledge documentation in the Iranian medical university libraries by using structural equation modeling - Omid Chehri; Alireza Isfandyari-Moghaddam; Seyed Aliakbar Famil Rohani; Faramarz Soheili (Golestan University of Medical Sciences, 2023)
Background: Organizational knowledge management requires a structure or framework to identify, extract and document knowledge. The review of knowledge management sources shows that since the late 1980s, several cycles have been introduced in the field of knowledge management, and the Mayer and Zack cycle has been one of the most important cycles. The purpose of this study was to design a model for documenting organizational experiences based on the view of point of Iranian libraries managers in medical sciences universities by using Mayer and Zack model. Methods: The research method was survey and correlation schemes are used. The population of the study consisted of 209 managers and heads of central and hospital libraries. Sampling was a stratified random sampling method. data gathering was done in 2022 by questionnaire. path- analyses and structural equation modeling was used to data analyses. RMS-Theta measure was used to test the model. Results: The results of the partial least squares test showed that the gathering knowledge and Knowledge refinement has a significant effect on knowledge documentation. Knowledge refinement had the highest and knowledge application had the lowest impact on knowledge documentation. Conclusion: The results confirmed the effects of knowledge collection and refinement on knowledge documentation. Therefore, it is possible to rely on the designed model and effective factors of knowledge documentation and generalize the obtained results for knowledge documentation in libraries and information centers.